Management of severe ME/CFS in children and young people in the UK: a British Paediatric Surveillance Unit study - Amberly Brigden; Ilaria Idini; Alexander Peter Royston; Sarah Burge; Katharine Claire Pike (BMJ Publishing Group, 2024)
Objective Severe myalgic encephalomyelitis or chronic fatigue syndrome (ME/CFS) in children and young people (CYP) is a little-understood condition which significantly impacts education, development and quality of life. We used data from a population-wide surveillance study to explore the screening investigation, referral and management of suspected cases of paediatric severe ME/CFS.Methods A British Paediatric Surveillance Unit (BPSU) study reported cases of CYP with suspected severe ME/CFS between February 2018 and February 2019. Paediatricians reporting cases to BPSU and allied healthcare professionals in two large specialist paediatric ME/CFS centres were invited to complete questionnaires for CYP meeting the surveillance case definition. The study focused primarily on CYP with confirmed severe ME/CFS and the extent to which their care met NICE (The National Institute for Health and Care Excellence) recommendations but also considered separately those with probable or possible severe ME/CFS.Results This study includes a total of 92 CYP with suspected severe ME/CFS; 33 meeting criteria for severe ME/CFS and an additional 59 classified as probable or possible severe ME/CFS. For 16 possible cases, incomplete investigation to exclude alternative diagnoses prevented confirmation of a severe ME/CFS diagnosis. Only 21 of 33 (64%) confirmed severe ME/CFS cases had been referred to specialist services. The management provided varied considerably between patients and four received nothing at all. Of the management provided, the most frequent approaches were medication (67%), activity management (61%) and physiotherapy (61%). Domiciliary assessments and support, and social services referrals were received by 12% and 6% of confirmed severe cases. Similar proportions of management approaches were seen in probable/possible severe ME/CFS.Conclusion Full investigation is frequently incomplete in CYP with suspected severe ME/CFS and recommendations for referral and management are poorly implemented, in particular the needs of CYP who are unable to leave their home might be poorly met.